Genome-wide identification, phylogenetic and expression pattern analysis of HSF family genes in the Rye (Secale cereale L.) - Yanyan Ren; Rui Ma; Muhua Xie; Yue Fan; Liang Feng; Long Chen; Hao Yang; Xiaobao Wei; Xintong Wang; Kouhan Liu; Peng Cheng; Baotong Wang (BMC Plant Biology, 2023)
Abstract Background Heat shock factor (HSF), a typical class of transcription factors in plants, has played an essential role in plant growth and developmental stages, signal transduction, and response to biotic and abiotic stresses. The HSF genes families has been identified and characterized in many species through leveraging whole genome sequencing (WGS). However, the identification and systematic analysis of HSF family genes in Rye is limited. Results In this study, 31 HSF genes were identified in Rye, which were unevenly distributed on seven chromosomes. Based on the homology of A. thaliana, we analyzed the number of conserved domains and gene structures of ScHSF genes that were classified into seven subfamilies. To better understand the developmental mechanisms of ScHSF family during evolution, we selected one monocotyledon (Arabidopsis thaliana) and five (Triticum aestivum L., Hordeum vulgare L., Oryza sativa L., Zea mays L., and Aegilops tauschii Coss.) specific representative dicotyledons associated with Rye for comparative homology mapping. The results showed that fragment replication events modulated the expansion of the ScHSF genes family. In addition, interactions between ScHSF proteins and promoters containing hormone- and stress-responsive cis-acting elements suggest that the regulation of ScHSF expression was complex. A total of 15 representative genes were targeted from seven subfamilies to characterize their gene expression responses in different tissues, fruit developmental stages, three hormones, and six different abiotic stresses. Conclusions This study demonstrated that ScHSF genes, especially ScHSF1 and ScHSF3, played a key role in Rye development and its response to various hormones and abiotic stresses. These results provided new insights into the evolution of HSF genes in Rye, which could help the success of molecular breeding in Rye.